Neofici żydowscy w Łodzi w XIX wieku - Gawryszczak, Anna (Acta Universitatis Lodziensis. Folia Historica, 2014)
The present article is bringing up the issues associated with the onomastics of the Jewish population, but first of all the issues inseparably being associated with these issues concerning the proselytism. In it an attempt to look at reasons a Jewish population was guided by which in the result was made apostasy or the conversion to their more distant life had converting to other faith and what influence. In it mechanisms of coming into existence of surnames of Jewish neophytes and manners of the formation of their derivative forms were expressed. The article is showing, that with the Jewish origin adopting the Christian religion along with the change has most often been a met manner of ‘breaking’ faith was being adopted new names, current at that time also in an small number in Łódź. At first, still in the 18th century converts dressed names from the godparents. They were also being created from: of months (e.g. Czerwiński), weekdays (e.g. Niedzielski), towns (e.g. Lowicki), of sign in the coat of arms (of especially a cross e.g. Krzyżanowski), name Jewish and Christian (e.g. Jakubowski), accepted from of ‘goodwill of baptism’ (e.g. Dobrowolski). Incipient surnames are also attesting to neophytes ‘anew’ (e.g. Nowicki), created from common words of the type: stranger (e.g. Przybylowicz), as well as containing the suffix -ski be -cki (e.g. Krysinski). Besides exchanged ways of creating new forms a row of other surnames also exists, of which origins we aren’t able to establish. It is necessary however to remember, that wanting to make correct semantic analysis definite ‘names’, one should exactly read the genesis of the entire family. It is necessary also to take into account what some researchers are underlining, that surnames characteristic of neophytes not always can attest to their Jewish origin.